Randomized clinical trial of negative pressure wound therapy as an adjunctive treatment for small‐area thermal burns in children. Issue 13 (14th September 2020) - Frear, C. C.; Cuttle, L.; McPhail, S. M.; Chatfield, M. D.; Kimble, R. M.; Griffin, B. R.
Abstract : Background: The efficacy of negative pressure wound therapy (NPWT) in the acute management of burns remains unclear. The purpose of this trial was to compare standard Acticoat™ and Mepitel™ dressings with combined Acticoat™, Mepitel™ and continuous NPWT to determine the effect of adjunctive NPWT on re‐epithelialization in paediatric burns. Methods: This two‐arm, single‐centre RCT recruited children with acute thermal burns covering less than 5 per cent of their total body surface area. The primary outcome was time to re‐epithelialization. Blinded assessments were performed using photographs captured every 3–5 days until discharge. Secondary measures included pain, itch, grafting, perfusion and scar management referrals. Results: Some 114 patients were randomized. Median time to re‐epithelialization was 8 (i.q.r. 7–11) days in the NPWT group and 10 (8–14) days in the control group. In a multivariable model, NPWT decreased the expected time to wound closure by 22 (95 per cent c.i. 7 to 34) per cent ( P  = 0·005). The risk of referral to scar management was reduced by 60 (18 to 81) per cent ( P  = 0·013). Four participants in the control group and one in the NPWT group underwent grafting. There were no statistically significant differences between groups in pain, itch or laser Doppler measures of perfusion. Adverse events were rare and minor, although NPWT carried a moderate treatment burden, with ten patients discontinuing early. Conclusion: Adjunctive NPWT hastened re‐epithelialization in small‐area burn injuries in children, but had a greater treatment burden than standard dressings alone. Registration number: ACTRN12618000256279 ( http://ANZCTR.org.au ). Abstract : In this RCT, children with small‐area thermal burns were randomized to standard silver‐impregnated dressings or standard dressings in conjunction with continuous negative pressure wound therapy (NPWT). Adjunctive NPWT decreased time to re‐epithelialization, with attendant improvements in dressing change requirements and scar management referrals. There were no statistically significant differences in pain, itch, or laser Doppler measures of perfusion. Negative pressure wound therapy hastens epithelialization Abstract : Antecedentes: La eficacia del tratamiento de las heridas con presión negativa ( negative pressure wound therapy, NPWT) en el tratamiento agudo de las quemaduras sigue sin estar claro. El propósito de este ensayo clínico fue comparar los apósitos estándar del tipo Acticoat™ y Mepitel™ con la combinación de Acticoat™, Mepitel™ y NPWT continua para determinar el efecto de la adición de NPWT en la reepitelización de las quemaduras en pediatría. Métodos: Ensayo controlado y aleatorizado, con dos brazos y unicéntrico, que reclutó niños con quemaduras térmicas agudas que afectaban < 5% de la superficie corporal total. El resultado primario fue el tiempo hasta la reepitelización. Se realizaron evaluaciones a ciegas utilizando fotografías tomadas cada 3‐5 días hasta el alta hospitalaria. Las medidas secundarias incluían dolor, picor, injerto, perfusión y derivación para el tratamiento de las cicatrices. Resultados: Se aleatorizaron un total de 114 pacientes. La mediana de tiempo hasta la reepitelización fue 8 días (rango intercuartílico, interquartile range, IQR 7‐11) en el grupo NPWT y 10 días (8‐14) en el grupo control. En el modelo multivariable, el uso de NPWT disminuyó los días previstos hasta el cierre de la herida en un 22% (i.c. del 95% 7‐34%; P = 0, 005). El riesgo de ser derivado para el tratamiento de la cicatriz se redujo en un 60% (18‐81%; P = 0, 013). Cuatro participantes en el grupo control y uno en el grupo NPWT fueron sometidos a injertos. No hubo diferencias estadísticamente significativas en el dolor, picor, o mediciones de la perfusión con Doppler laser. Los eventos adversos fueron raros y menores, aunque NPWT conllevó una carga de tratamiento moderada con 10 pacientes que lo suspendieron precozmente. Conclusión: El tratamiento complementario de la herida con presión negativa acelera el tiempo hasta la reepitelización en quemaduras de pequeña extensión en niños, pero implica una mayor carga de tratamiento.